Effect of Application Time of Two Different Disinfectants on the Surface Roughness of an Elastomeric Impression Material - Karaman, Tahir; Oztekin, Faruk; Tekin, Samet (Premchand Shantidevi Research Foundation, 2020)
Introduction: Pathogens, such as cytomegalovirus, hepatitis B virus, hepatitis C virus, herpes simplex virus types 1 and 2, and human immunodeficiency virus, are transmitted, threatening the health of dental laboratory workers, especially as a result of saliva and blood contact of patients. To prevent cross-infection, impression materials should be disinfected at the end of the impression process in the mouth. Aim: To study the effect of application time of sodium hypochlorite and quaternary ammonium-based disinfectant solution on the surface roughness of an elastomeric impression material. Materials and Methods: In this in-vitro study done during March 2020, 10 disc-shaped samples were used in each group, with a total of 110 samples obtained from a light body elastomeric impression material with dimensions of 15x3 mm. The samples were kept in a sodium hypochlorite solution (Wizard; Rehber Kimya, Istanbul, Turkey) at concentrations of 1% and 5% for 1, 5, 10, and 30 minutes and in a quaternary ammonium-based disinfectant (Zeta 7 Solution, Zhermack SpA, Italy) for 10 and 30 minutes. Surface roughness measurements were taken with a profilometer device. The data obtained were statistically analysed by Kolmogorov-Smirnov test and Wilcoxon signed rank test for dependent/paired groups for the continuous data. The significance level was set to alpha=0.05. Results: A statistically significant difference was found between the control group and the 1% sodium hypochlorite (30 min p-value 0.037), and 5% sodium hypochlorite (30 min p-value 0.017). The statistical evaluation of the surface roughness of the samples with different concentrations of sodium hypochlorite and the same times was done and found statistically significant at 30 mins. p-value 0.021. Conclusion: The prolonged application of the sodium hypochlorite disinfectant at 1% and 5% concentrations caused a significant increase in the light body elastomeric impression material's surface roughness.
Keywords: Ammonium-based disinfectant; Chemical disinfection; Cross-infection; Disinfection times; Sodium hypochlorite